2000
DOI: 10.3310/hta4140
|View full text |Cite
|
Sign up to set email alerts
|

The determinants of screening uptake and interventions for increasing uptake: a systematic review.

Abstract: T he overall aim of the NHS R&D Health Technology Assessment (HTA) programme is to ensure that high-quality research information on the costs, effectiveness and broader impact of health technologies is produced in the most efficient way for those who use, manage and work in the NHS. Research is undertaken in those areas where the evidence will lead to the greatest benefits to patients, either through improved patient outcomes or the most efficient use of NHS resources. The Standing Group on Health Technology a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
282
0
3

Year Published

2003
2003
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 235 publications
(298 citation statements)
references
References 206 publications
(1,567 reference statements)
13
282
0
3
Order By: Relevance
“…This was demonstrated by the positive and signifi cant association of all lagged dependent variables. The experience of previous screenings on health check-ups has been found to be a key factor in the literature [26]. It seems that there is an important distinction between individuals who have never accessed health services and those with previous experiences.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This was demonstrated by the positive and signifi cant association of all lagged dependent variables. The experience of previous screenings on health check-ups has been found to be a key factor in the literature [26]. It seems that there is an important distinction between individuals who have never accessed health services and those with previous experiences.…”
Section: Discussionmentioning
confidence: 99%
“…Int J Public Health 53 (2008)[23][24][25][26][27][28][29][30] Do income effects mask social and behavioural factors when © Birkhäuser Verlag, Basel, 2008 looking at universal health care provision?…”
mentioning
confidence: 99%
“…Based on previous research, a set of socio-demographic and medical variables was included in the analysis, as predictors of mammography utilization (Borras, Guillen, Sanchez, Junca, & Vicente, 1999;Cabeza, Esteva, Pujol, Thomas, & Sanchez-Contador, 2007;Chiu, 2003;Farmer, Reddick, D'Agostino, & Jackson, 2007;George, 2000;Hay, Buckley, & Ostroff, 2005;Jepson et al, 2000;Katapodi, Lee, Facione, & Dodd, 2004).…”
Section: Methodsmentioning
confidence: 99%
“…The involvement of general practitioners (GP) or family practitioners has been recommended by several guidelines about screening program organisation [4][5][6]. Even though GPs are considered very important in any preventive practice because of their natural proximity to healthy beneficiaries, several studies have shown that GPs are not always well informed about CRCS practice, a consistent percentage of them do not trust FOBTs as an effective screening tests and finally there is a large variability in the recommendations given to their beneficiaries about CRCS [7][8][9][10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%